The Australian national binge drinking campaign: campaign recognition among young people at a music festival who report risky drinking - Sacks-Davis Rachel; Gold Judy; Dietze Paul; van Gemert Caroline; Stoové Mark; Vally Hassan; Hellard Margaret (BMC, 2011)
Abstract Background The Australian Government launched a mass media campaign in 2009 to raise awareness of the harms and costs associated risky drinking among young Australians. The aim of this study was to assess if young people attending a music festival who report frequent risky single occasions of drinking (RSOD) recognise the key message of the campaign, "Binge drinking can lead to injuries and regrets", compared to young people who report less frequent RSOD. Methods A cross-sectional behavioural survey of young people (aged 16-29 years) attending a music festival in Melbourne, Australia, was conducted in January 2009. We collected basic demographics, information on alcohol and other drug use and sexual health and behaviour during the previous 12 months, and measured recognition of the Australian National Binge Drinking Campaign key message. We calculated the odds of recognition of the key slogan of the Australian National Binge Drinking Campaign among participants who reported frequent RSOD (defined as reported weekly or more frequent RSOD during the previous 12 months) compared to participants who reported less frequent RSOD. Results Overall, three-quarters (74.7%) of 1072 participants included in this analysis recognised the campaign message. In the adjusted analysis, those reporting frequent RSOD had significantly lower odds of recognising the campaign message compared to those not reporting frequent RSOD (OR 0.7, 95% CI 0.5-0.9), whilst females had significantly greater odds of recognising the campaign message compared to males (OR 1.8, 95% CI 1.4-2.1). Conclusions Whilst a high proportion of the target group recognised the campaign, our analysis suggests that participants that reported frequent RSOD - and thus the most important group to target - had statistically significantly lower odds of recognising the campaign message.